COMMERCIAL LAW IN THE CONTEXT OF ECONOMIC DEVELOPMENT: THE NIGERIAN EXPERIENCE - Fabunmi, J. O. (OAU PRESS, 2013)
Commercial activities persist endlessly in time of peace and war. Government may be overthrown in coups, wars may break out, national disasters may occur but somehow commercial activities continue on a regular basis. 1 Merchants have always found a way of continuing business relationships in any given situation. Their ingenuity in formulating new techniques to meet the challenges of changing economic climates is unparalleled. One significant example of this ingenuity is the fashioning of a distinct body of rules derived from customs and usages to govern the transactions of merchants